Faces of Joblessness in Italy: A People-Centred Perspective on Employment Barriers and Policies - Daniele Pacifico; James Browne; Rodrigo Fernandez; Herwig Immervoll; Dirk Neumann; Céline Thévenot (Institute of Labor Economics (IZA), 2018)
In the aftermath of the financial and economic crisis, large shares of working-age individuals in Italy either did not work or only to a limited extent. As the employment rate bottomed out in 2013, 32% were without employment during the entire year, and a further 7% had weak labour-market attachment, working only a fraction of the year, or on restricted working hours. This paper applies a novel method for measuring and visualising employment barriers of individuals with no or weak labour-market attachment, using household micro-data. It first develops indicators to quantify employment obstacles under three broad headings: (i) work-related capabilities, (ii) incentives, and (iii) employment opportunities. It then uses these indicators in conjunction with a statistical clustering approach to identify unobserved ("latent") groups of individuals facing similar combinations of barriers. The resulting typology of labour-market difficulties provides insights on the most pressing policy priorities in supporting different groups into employment. A detailed policy discussion illustrates the use of these empirical results to inform people-centred assessments of existing labour-market integration measures and of key challenges across different policy areas and institutions. The most common employment obstacles in Italy were limited work experience, low education and skill levels, and scarce job opportunities. Although financial disincentives, health limitations and care responsibilities were less widespread overall, they remained important barriers for some groups. A striking finding is that more than half of jobless or low-intensity workers face three or more simultaneous barriers, highlighting the limits of narrow policy approaches that focus on subsets of these employment obstacles in isolation.
Keywords: C38; H31; J2; J6; J8; 330; employment barriers; profiling; activation; policy coordination